2019
DOI: 10.3390/app9040752
|View full text |Cite
|
Sign up to set email alerts
|

Joint Pedestrian and Body Part Detection via Semantic Relationship Learning

Abstract: While remarkable progress has been made to pedestrian detection in recent years, robust pedestrian detection in the wild e.g., under surveillance scenarios with occlusions, remains a challenging problem. In this paper, we present a novel approach for joint pedestrian and body part detection via semantic relationship learning under unconstrained scenarios. Specifically, we propose a Body Part Indexed Feature (BPIF) representation to encode the semantic relationship between individual body parts (i.e., head, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…ose networks were able to learn but were too slow in practice to be useful in real-time applications; the technique in [12] showed that stochastic gradient descent by backpropagation was effective in training CNNs. CNNs became in use but fell out of fashion due to the support vector machine as in [21] and other simpler methods like linear classifiers as in [22]. New techniques that have been developed recently [23,24] show higher image classification accuracy in ImageNet large scale visual recognition [25].…”
Section: Related Workmentioning
confidence: 99%
“…ose networks were able to learn but were too slow in practice to be useful in real-time applications; the technique in [12] showed that stochastic gradient descent by backpropagation was effective in training CNNs. CNNs became in use but fell out of fashion due to the support vector machine as in [21] and other simpler methods like linear classifiers as in [22]. New techniques that have been developed recently [23,24] show higher image classification accuracy in ImageNet large scale visual recognition [25].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, there are a variety of applications, including video surveillance, intelligent transportation systems, and self-driving assistance systems. Though there are many significant improvements for detecting pedestrians, the crucial yet challenging problems include the large variety of poses, appearances, sizes, and types of occlusions [4]- [6]. Among these problems, partial occlusion frequently occurs due to the diversity of the partially occluded patterns of the pedestrians, and it needs further investigation between the pedestrians and the crowded instances.…”
Section: Introductionmentioning
confidence: 99%
“…Pedestrian detection has attracted considerable attention from researchers in computer vision. Although many studies in pedestrian detection areas have been reported during the past decade [1][2][3][4][5][6][7][8], most of them are confined to detecting pedestrians during daytime using visible (VI) cameras. However, the performance of VI cameras depends on good illumination conditions and can be affected when illumination is poor.…”
Section: Introductionmentioning
confidence: 99%